NAGARI DEVICE DRIVERS ABILITY IN DEVELOPMENT IN NAGARI PUNGGASAN NAGARI LINGGO EASTERN DISTRICT OF SOUTH COASTAL DISTRICT SARI BAGANTI - Juprida, Juprida; Drs. Edi Suarto, M.Pd, Drs. Edi Suarto, M.Pd; Yuherman, SP., M.Pd, Yuherman, SP., M.Pd (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This study aims to find out about Incentives Device Capabilities In building have Nagari Nagari Nagari East Punggasan Linggo Sari subdistrict Baganti South Coastal District . Incentives Capability Development Tools In Nagari Nagari , motivational devices villages in village development and village participation in the development of the village .This research is qualitative . Informants in this study is the village . Key informants consisted of the village cadres . The technique of determining the informant by researchers is purposife sampling .The results of research in the field as follows : a) the ability Incentives Nagari village in development . The lack of the ability of villages in development and lack of funds to carry out development . b ) Work motivation in the development of the village . Lack of motivation in the development of the village is to make the village more advanced there should be a motivation of its people as well . c ) Participation in the development of devices work Nagari Nagari . Participation will be undertaken in the development of the villages villages is low according to key informants , and they alone are not enough participation also requires the participation of communities , community participation here is very less so because the village can not raise the participation of the community .Â